The sensitivity of DPD scintigraphy to detect transthyretin cardiac amyloidosis in V30M mutation depends on the phenotypic expression of the disease - Coutinho, Maria Conceição Azevedo (2020)
© 2020 Informa UK Limited, trading as Taylor & Francis Group.